The Effect of Temperature and Thermodynamic Parameters on the Ionization Constants of Some Imines Derived from Vanillin with substituted aniline - Rawaa Daoud Sulaiman; Zaheda Ahmed Najim (Tikrit Journal of Pure Science, 2022)
This work presents a method for the preparation of imine compounds including Schiff bases derived from vanillin with aniline, o-nitroaniline, o-tolidene and o-chloroaniline. Compounds' structures of the prepared compounds were confirmed by physical methods like melting point, infrared spectroscopy (IR), electronic spectroscopy (U.V), and nuclear magnetic resonance spectroscopy (NMR).